Exploration of Bird Diversity Potential for Birdwatching Ecotourism in Bangbayang Village, Sumedang, West Java - Ramadani, Annisa; Assalam, Muhammad Hudan; Putra, Indeka Dharma; Agustin, Dini; Fahira, Adinda Putri Awalia; Friscila, Sulastri; Qotrunnada, Ananda (Universitas Nasional Jakarta, 2024)
Sumedang was one of the districts in West Java Province that consisted of 26 sub-districts, 7 neighborhoods, and 270 villages. Bangbayang Village, located in the Situraja neighborhood, was one of the villages with ecotourism potential that had not been fully developed. The topography of the village, characterized by hills, had its own charm, and its biodiversity had not been widely explored. One aspect of this biodiversity that had potential for ecotourism was the diversity of bird species found there. Therefore, the research aimed to explore the potential and diversity of birds in Bangbayang Village, Sumedang, in the context of developing birdwatching science and ecotourism. The research was conducted in January 2023. Birds were observed using the point count method, and the data were analyzed for conservation status, the Shannon-Wiener species diversity index, the Margalef richness index, bird species evenness, and the Simpson dominance index. The results identified 35 species of birds from 20 families, 12 of which were endemic to Indonesia. Among them, two species were classified as NT (Near Threatened), two as EN (Endangered), six were included in the CITES Appendix II category, and eight species were protected under Ministerial Regulation P.106 of 2018. The diversity index, species richness index, and evenness index values were high, recorded at 3.343, 7.575, and 0.940, respectively, while no bird species dominated, with a dominance index value of 0.043. Based on their status, nine species were identified as having potential for ecotourism attraction: the black eagle, javan hawk-eagle, crested serpent-eagle, oriental honey-buzzard, flame-fronted barbet, black-banded barbet, bar-winged prinia, black-thighed falconet, and java sparrow.